Structure and nanotoxicity of fungal chitin-glucan nanofibrils with gradient acid and alkaline treatments - Cadavid Vargas, Juan Fernando (2025)
Among nanoscale biopolymers, fungal chitin nanofibrils (ChNFs) stand out for their low carbon footprint and functional properties. However, the nanotoxicity properties of ChNFs have not been fully elucidated. To fill this knowledge gap, here we investigate the cytotoxicity and inflammatory effects of chemically modified ChNFs having gradient acid and alkaline treatments. ChNFs isolated from white mushroom exhibit a long fibrous morphology with diameters of 3–8 nm and lengths of 150–600 nm, and are composed of α-chitin in coexistence with amorphous covalently bounded β-glucans. Both alkaline (2 m NaOH) and acidic (2 m HCl) treatments impact the crystallinity, N-acetylation, zeta potential, and nitrogen content values to provide ranges of 23-to-51 %, 45-to-99 %, −5 to +26 mV, and 2.6-to-5.2 %, respectively. Nanotoxicity studies with colloidal dispersions demonstrate differences in the inflammatory response by cells after chemical post-treatments. The NaOH-treated ChNFs elicited a much lower inflammatory response, attenuating the release of nitrites and the pro-inflammatory cytokine tumor necrosis factor-α (TNF-α). Alginate hydrogels with ChNFs were further fabricated and demonstrated potential to host cells in three-dimensional microenvironments, preserving a good metabolic activity, viability, and cell proliferation. These results may guide new applications of fungal nanochitin in pharmaceutical or tissue engineering.